Intellectual Capital Thrives, Tax Audit Drives? The Moderating Role of Information and Technology on Tax Audit Quality - Yusrifalda, Amalia; Firmansyah, Amrie (APSSAI ACCOUNTING REVIEW, 2024)
Research aims: This study examines the influence of intellectual capital on tax audit quality at the Directorate General of Taxes and explores the potential moderating role of information technology in the relationship between intellectual capital and tax audit quality. Design/Methodology/Approach: Focusing on public human capital (PHC), public structural capital (PSC), and public relational capital (PRC), the study employs PLS-SEM analysis on primary data obtained from 35 Tax Auditors (FPP) in the DKI Jakarta region. Research findings:  The results show that PRC has a positive effect on tax audit quality, while PHC and PSC do not have a significant impact on tax audit quality. Furthermore, no moderating effect of information technology was found on the relationship between PHC, PSC, or PRC and tax audit quality. Theoretical contribution/Originality: This study findings highlight the importance of building strong relationships to enhance tax audit quality, while human and structural capital plays no significant role in this context. Practitioner/Policy implication: The study recommends integrating technology and optimizing business processes by the Directorate General of Taxes to achieve high-quality tax audits. Additionally, the findings can enrich policymakers' insights to improve the efficiency and effectiveness of the policies implemented and foster further discussion on managing intellectual capital to achieve sustainable public sector goals in Indonesia.